Sovereign Debt Composition in Advanced Economies : A Historical Perspective - Abbas, S. M. Ali.; Blattner, Laura; De Broeck, Mark.; ElGanainy, Asmaa (Washington, D.C. : International Monetary Fund, 2014)
We examine how the composition of public debt, broken down by currency, maturity, holder profile and marketability, has responded to major debt accumulation and consolidation episodes during 1900-2011. Covering thirteen advanced economies, we focus on debt structure shifts that occurred around the two World Wars and global economic downturns, and the subsequent debt consolidations. Notwithstanding data gaps, we are able to recover some broad common patterns. Episodes of large debt accumulation-essentially, large increases in debt supply- were typically absorbed by increases in short-term, foreign currency-denominated, and banking-system-held debt. However, this pattern did not hold during the debt build-ups starting in the 1980s and 1990s, which were compositionally skewed toward long-term local-currency debt. We attribute this change to higher structural demand for sovereign paper, linked to capital account liberalization in advanced economies, the emergence of a large contractual saving sector, and innovative sovereign debt products. With regard to debt consolidations, we find support for the financial repression-cum-inflation channel for post World War II debt reductions. However, the scope for a repeat of this strategy appears limited unless financial liberalization and globalization were materially rolled back or the current globally agreed monetary policy regime built around price stability abandoned. Neither are significant favorable structural demand shifts, as witnessed in the 1980s and 1990s, likely.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet